2013
DOI: 10.1108/ejm-10-2011-0564
|View full text |Cite
|
Sign up to set email alerts
|

The value of health and wellbeing: an empirical model of value creation in social marketing

Abstract: Purpose -The purpose of this paper is to investigate the role of multiple actors in the value creation process for a preventative health service, and observe the subsequent impact on key service outcomes of satisfaction and customer behaviour intentions to use a preventative health service again in the future. Design/methodology/approach -An online self-completion survey of Australian women (n ¼ 797) was conducted to test the proposed framework in the context of a free, government-provided breastscreening serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
154
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(170 citation statements)
references
References 58 publications
9
154
2
5
Order By: Relevance
“…Interestingly, the co-creation of emotional value emerged from the data. This is in contrast to previous cancer screening research which finds functional value (the utility of safeguarding one's health through screening) to be a stronger influence on perceived value and satisfaction than emotional value (Zainuddin et. al., 2013;.…”
Section: Proposition 4: Internal Health Locus Of Control Affects Emotcontrasting
confidence: 99%
“…Interestingly, the co-creation of emotional value emerged from the data. This is in contrast to previous cancer screening research which finds functional value (the utility of safeguarding one's health through screening) to be a stronger influence on perceived value and satisfaction than emotional value (Zainuddin et. al., 2013;.…”
Section: Proposition 4: Internal Health Locus Of Control Affects Emotcontrasting
confidence: 99%
“…According to Bettencourt (1997), a successful service creation requires that customers be cooperative, observing rules and policies, and accepting directions from employees. In health care service, responsible behavior manifests in cooperating with diagnostic efforts or other activities such as positioning the body according to the instructions of the radiographers to obtain a chest screen, taking medicaments as prescribed (Zainuddin et al 2013). In higher education service, examples of responsible behavior include home readings or doing assignments, taking part in class meetings.…”
Section: Customer Participation Behaviorsmentioning
confidence: 99%
“…As shown in Figure 2B, activity was significantly associated with behavioural intentions through clarity (β = .08 [.00, .22 These qualities are likely to make these services appear to be responsive to consumers' needs and wants, rather than simply reactive. In health services, this can refer to the interpersonal quality of the service employees who come into direct contact with clients (Dagger et al, 2007), which has been found to be an important quality to preventative health service users like breastscreening (Zainuddin et al, 2013). Both relationships are partially mediated by the BPA of clarity, suggesting that a simple, easily understood brand message about the responsibility and activity of a service will impact consumers' intentions to use the service in the future.…”
Section: ])mentioning
confidence: 99%